The Effect of Cow State Fertilizer and Mutiara NPK to Plant Growth and Production of Purple Eggplant (Solanum melongena L.) on Alluvial Soil in Polybag - Sri Rahayu; Setiawan Setiawan; Jojo Kusna (International Journal of Multi Discipline Science, 2021)
This study aims to determine the effect of the interaction of cow state fertilizer and Mutiara NPK to plant growth and production of purple eggplant on alluvial soil in polybags. This research was conducted on Karet Street, West Pontianak District, West Kalimantan Province with an altitude of ± 1 meter above sea level. This research was conducted from March 25 to July 2, 2021. This study used a completely randomized design (CRD) with a factorial pattern consisting of 2 factors. The first factor is cow state fertilizer (S) with 3 levels, namely s1 = 40 grams/polybag, s2 = 60 grams/polybag and s3 = 80 grams/polybag. The second factor is Mutiara NPK fertilizer (N) with 3 levels, namely n1 = 1,2 grams/polybag, n2 = 1,6 grams/polybag and n3 = 2 grams/polybag. The number of treatments in this study was 9 treatment combinations and each treatment consisted of 3 times. Each replication consisted of 3 plant samples, so the total number of plant samples was 81 plants. The variables observed in this study were plant height (cm), number of leaves per plant (strands), number of fruits per plant (fruit), and fruit weight per plant (grams). The results showed that cow state fertilizer treatment had a significant effect on the number of leaves per plant, a very significant effect on fruit weight per plant, and no significant effect on the number of plants and fruit per plant. Mutiara NPK fertilizer treatment had a significant effect on fruit weight per plant and had no significant effect on plant height, number of leaves per plant, and number of fruit per plant. The interaction of cow state fertilizer and Mutiara NPK had a significant effect on fruit weight per plant and had no significant effect on plant height, number of leaves per plant, and number of fruit per plant.